Marriage Contracts via Video Call: A Comparative Analysis of the Fatwas of Nahdlatul Ulama’s Bahtsul Masa’il and Muhammadiyah’s Majelis Tarjih in Lampung - Nur Edi, Relit; Susiadi; Ardian Nurhuda (SMART: Journal of Sharia, Traditon, and Modernity, 2023)
Marriage (akad nikah) as a mitsāqan ghalīẓan requires the fulfillment of specific pillars and conditions, one of which is ittihād al-majlis between ijāb and qabūl. A legal challenge arises when the classical concept of ittihād al-majlis is confronted with the reality of virtual spaces that eliminate physical boundaries while enabling simultaneous audio-visual interaction. This study aims to conduct a comparative analysis of the perspectives of the Lembaga Bahtsul Masail of Nahdlatul Ulama and the Majelis Tarjih of Muhammadiyah in Lampung Province regarding the legal validity of marriage contracts conducted through video call media. Employing a qualitative field research design with descriptive-analytical and comparative approaches, the data were collected through interviews with institutional representatives as well as document analysis of fatwas, classical and contemporary fiqh literature, and relevant marriage regulations. The findings indicate that the Lembaga Bahtsul Masail of Nahdlatul Ulama interprets ittihād al-majlis as requiring physical unity of place and emphasizes the principle of legal prudence, thereby considering online marriage contracts invalid unless conducted through a mechanism of representation (wakālah). In contrast, the Majelis Tarjih of Muhammadiyah conceptualizes ittihād al-majlis as temporal continuity and clarity of communication between ijāb and qabūl, thus regarding online marriage contracts as legally valid provided that all pillars and conditions of marriage are duly fulfilled.